PENGUATAN KOMPETENSI PERSONIL: PELATIHAN PENULISAN KARYA TULIS ILMIAH BAGI TNI SATJAR BRIGIF PARA RAIDER 3/TBS KOSTRAD KARIANGO MAROS - Gustaf Said, Try; Satriani Is, Sitti; Agustan; B Syamsuddin, Yati; Baharuddin; Carsel, Syamsuni (LPPM Universitas Islam 45 Bekasi, 2024)
Scientific papers are generally carried out by academics, but over time in the 21st century today the writing of scientific papers is also required in State defense institutions such as the TNI. Writing scientific papers is relatively new for the TNI, therefore intense, systematic and planned training is needed to provide in-depth knowledge about the procedures for writing scientific papers to the TNI. At Kostrad Kariango Maros is located in Sudirman Village, Tanra Lili District, Maros Regency, at Kostrad, Kariango 1 battalion consists of 2500 personnel, but the focus of the PKM is TNI personnel who serve as staff, non-commissioned officers and officers in the Brigif Denma unit. The purpose of implementing community service is to provide theory to the TNI about the importance of writing scientific papers, qualitative research material in writing scientific papers, training in good and correct article writing ethics, reviewing the use of good and correct Indonesian in writing scientific papers, and training in mendeley in writing scientific papers. The stages of activities proposed in the implementation of the PKM are the preparation stage, assessment stage, alternative activity planning stage, formulation stage, action plan, activity implementation stage, evaluation stage, and termination stage. The output of the PKM is in the form of youtube, newspapers, PKM is published in accredited national journals. The implementation of the PKM went according to plan. The PKM results show that scientific writing training for TNI Satjar personnel of Brigif Para Raider 3/TBS Kostrad Kariango Maros has an important role in increasing the professionalism and competence of personnel.